2019
DOI: 10.3389/fimmu.2019.02347
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Chelation Specifically Inhibits Early Stages of Dengue Virus Replication by Activation of NF-κB and Induction of Antiviral Response in Epithelial Cells

Abstract: Zinc is an essential micronutrient which regulates diverse physiological functions and has been shown to play a crucial role in viral infections. Zinc has a necessary role in the replication of many viruses, however, antiviral action of zinc has also been demonstrated in in vitro infection models most likely through induction of host antiviral responses. Therefore, depending on the host machinery that the virus employs at different stages of infection, zinc may either facilitate, or inhibit virus infection. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 57 publications
(66 reference statements)
1
51
0
Order By: Relevance
“…It is puzzling that Zn 2+ both promotes and inhibits virus replication, while its deficiency is associated with increased viral load, suggesting that there are major gaps in our understanding of how this metal influences viruses. While Zn 2+ is required for virus replication, its chelation inhibits viral proteins (HPV E6 protein, flavivirus NS5A protein) and virus replication (HPV, dengue virus (DENV), and Japanese encephalitis virus (JEV)) [ 207 , 208 , 209 , 210 ]. Despite severe toxicities associated with experimental Zn 2+ chelators, such as TPEN (N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine) and 1,6-hexanediol, other drug classes with better safety profiles, including bananins, may be effective against HIV-1 and other viruses, including coronaviruses [ 211 , 212 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is puzzling that Zn 2+ both promotes and inhibits virus replication, while its deficiency is associated with increased viral load, suggesting that there are major gaps in our understanding of how this metal influences viruses. While Zn 2+ is required for virus replication, its chelation inhibits viral proteins (HPV E6 protein, flavivirus NS5A protein) and virus replication (HPV, dengue virus (DENV), and Japanese encephalitis virus (JEV)) [ 207 , 208 , 209 , 210 ]. Despite severe toxicities associated with experimental Zn 2+ chelators, such as TPEN (N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine) and 1,6-hexanediol, other drug classes with better safety profiles, including bananins, may be effective against HIV-1 and other viruses, including coronaviruses [ 211 , 212 ].…”
Section: Resultsmentioning
confidence: 99%
“…Despite severe toxicities associated with experimental Zn 2+ chelators, such as TPEN (N,N,N′,N′-tetrakis(2-pyridinylmethyl)-1,2-ethanediamine) and 1,6-hexanediol, other drug classes with better safety profiles, including bananins, may be effective against HIV-1 and other viruses, including coronaviruses [ 211 , 212 ]. Zn 2+ ionophores, such as pyrithione and chloroquine derivatives, among others, have also recently been shown to inhibit diverse groups of viruses, such as HSV, DENV, and SARS-CoV-2 [ 210 , 213 , 214 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 242 , 243 , 244 ]. Zinc supplementation is also effective in decreasing oxidative stress [ 245 , 246 ], in shortening the duration of cold symptoms in adults [ 247 ], and was found to have a direct antiviral effect on RSV [ 248 ], Dengue virus [ 249 ], and coronaviruses [ 250 ]. Lastly, some authors suggested that a combination of chloroquine with zinc might enhance chloroquine’s toxicity on viruses [ 249 , 250 , 251 , 252 ].…”
Section: Zincmentioning
confidence: 99%
“…Zinc supplementation is also effective in decreasing oxidative stress [ 245 , 246 ], in shortening the duration of cold symptoms in adults [ 247 ], and was found to have a direct antiviral effect on RSV [ 248 ], Dengue virus [ 249 ], and coronaviruses [ 250 ]. Lastly, some authors suggested that a combination of chloroquine with zinc might enhance chloroquine’s toxicity on viruses [ 249 , 250 , 251 , 252 ]. Te Velthius et al [ 249 ] reported that the combination of Zn2+ and zinc-ionophores like pyrithione can increase the intracellular Zn2+ concentration, and thus inhibits the replication of SARS-coronavirus (SARS-CoV) and equine arteritis virus in cell culture.…”
Section: Zincmentioning
confidence: 99%
See 1 more Smart Citation